TINJAUAN FAKTOR INTERNAL DAN EKSTERNAL PENYEBAB KESULITAN BELAJAR BIOLOGI SISWA KELAS VIII SMPN 2 BAYANG KECAMATAN BAYANG KABUPATEN PESISIR SELATAN - Guswita, Lira; Risdawati, M.Si., Dra. Hj. Renny; Nerita, S.Pd, M.Pd, Siska (STKIP PGRI Sumbar, 2014)
ABSTRACTÂ Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Internal and Â external Â factors Â are Â factors that Â exist Â inÂ eachÂ of the Â individual Â itself. Â ManyÂ factors influence the results of learning biology of the students, including internal and external factors. Based on the observations that have done by the researcher at Junior High School 2 Bayang there were information that the students got difficulty in biology from internal such as lack of interest, motivation, time management, and maintaining health. Then, from external such as lack of attention from parents and less environmental support caused students were lazy to learn. Consequently directly and indirectly have an effect to the studentsâ achievement. The purpose of this research was to review internal and external factors the causes of studentsâ difficulties in learning Biology for grade VIII Junior High School 2 Bayang Pesisir Selatan Regency.The design of this research was descriptive. The population of this research was the students for grade VIII Junior High School 2 Bayang Pesisir Selatan Regency in academic year 2013/2014 and the total number of the students was 203. Then, the sample was 30% or 61 students from 203 students. The technique was random sampling. Each student was randomly taken by using a lottery. The lottery will be drawn as the research sample.The percentages of the data based on the findings of this research were internal factors 66,03% with influential criteria, for external factors were: percentage of family factor 75,7% with influential criteria, percentage of school factor 65,9% with influential criteria, percentage of society factors 71,32% wit h influential criteria. It can be concluded that the external factors gave the greater impact to the studentsâ difficulties in learning Biology for grade VIII Junior High School 2 Bayang Pesisir Selatan Regency by percentage 70,97%.Â